Pengalaman Guru Sekolah Luar Biasa Dalam Upaya Pencegahan Kekerasan Seksual Pada Disabilitas - Siska Bradinda Putri Sudirman; Irvan Afriandi; Gatot N. A. Winarno (Pusat Riset dan Inovasi Nasional, 2023)
Students with disabilities are one of the most the most pervasive threats to sexual abuse. Children with disabilities are more likely to experience sexual abuse compared to their peers without disabilities. Teachers have a professional role as a resource to deliver sexual education in schools. The purpose of this study is to explore the experience of the teacher in teaching the prevention of sexual abuse among children with special needs. The methodology used is a qualitative method with a phenomenological approach through in-depth interviews with 11 teachers and data analysis using thematic analysis. Three themes emerged summarizing teachers in special school experience in teaching the prevention of sexual abuse among student with special needs included education in preventing sexual abuse, teacher’s motivation, source of information and support. Most teachers revealed about touch dos and don'ts in the learning process, implementing individual learning programs, and support from parents and schools. The conclusions of this study showed that the experience of special school teachers in preventing sexual abuse is considered to have been done well. Sexual abuse prevention programs can be continuously promoted to encourage children's assertiveness in protecting themselves from the risk of sexual abuse.